Architecting Microsoft .NET solutions for the enterprise - Esposito, Dino, 1965- (Microsoft Press, 2009)
Make the right architectural decisions up frontand improve the quality and reliability of your results. Led by two enterprise programming experts, you'll learn how to apply the patterns and techniques that help control project complexityand make systems easier to build, support, and upgraderight from the start. Get pragmatic architectural guidance on how to:Build testability, maintainability, and security into your system early in the designExpose business logic through a service-oriented interfaceChoose the best pattern for organizing business logic and behaviorReview and apply the patterns.